Global Mechanisms for Sustaining and Enhancing PES Schemes - Farley, Josh; Aquino, Andre; Daniels, Amy; Moulaert, Azur; Lee, Dan; Krause, Abby (2012)
An international payment for ecosystem service (IPES) schemes may be one of the only mechanisms available to stimulate the provision of vital non-marketed ecosystem services at the global level, as those nations that benefit from global ecosystem services (GES) cannot readily force other sovereign nations to provide them. Currently, international trade offers trillions of dollars in incentives for countries to convert natural capital into marketable goods and services, and few payments to entice countries to conserve natural capital in order to sustain critical non-marketed ecosystem services. We examine the biophysical characteristics of climate change and biodiversity to understand the obstacles to developing effective IPES schemes. We find that none of the existing schemes for providing GES are adequate, given the scale of the problem. A cap and auction scheme for CO2 emissions among wealthy nations could fund IPES and simultaneously deter carbon emissions. To disburse funds, we should adapt Brazil's ICMS ecologico, and apportion available funds to targeted countries in proportion to how well they meet specific criteria designed to measure the provision of GES. Individual countries can then develop their own policies for increasing provision of these services, ensured of compensation if they do so. Indirect IPES should include funding for freely available technologies that protect or provide GES, such as the low carbon energy alternatives that will be essential for curbing climate change. Markets rely on the price mechanism to generate profits, which rations technology to those who can afford it, reducing adoption rates, innovation and total value.